A Statistical Study of Intra-Domain and Trans-Domain Polymathy among Nobel Laureates. Issue 2 (2nd April 2020) - Root-Bernstein, Robert; Root-Bernstein, Michele
ABSTRACT: Polymathy may be defined as the productive pursuit of multiple endeavors, simultaneously or serially, across a lifetime. As such, polymathic breadth of interest across knowledge domains characterizes Nobel laureates in the sciences, literature, economics, and peace, though interest patterns vary between groups. Economics laureates, like science laureates, demonstrate significant trans-domain interests in mathematics and science but differ from scientists by focusing additional interests in the humanities and social sciences rather than in visual arts or crafts. Literature laureates share strong interests in visual arts with science laureates, but they engage far less in crafts and more in humanities. Literature laureates share with economics laureates a high interest in the humanities and social sciences but engage far less in the sciences. Peace laureates focus their multiple interests in the humanities and social sciences along with literature and economics laureates, but they differ from both by participating far less in arts or science. In addition, Nobel laureates are also intra-domain polymaths, engaging in more than one discipline within their primary field. Overall, Nobel laureates are significantly more likely to be trans- and intra-domain polymaths than the average person. Moreover, patterns of interest suggest that different professions select for or attract individuals with reasonably discrete combinations of talent.